Comparison of the Success Rate of External Dacryocystorhinostomy with Intramucosal Injection and Sponge Application of Mitomycin C to Circumosteal Mucosa - Khan, Faisal Aziz; Niazi, Shafaq Pervez; Hyder, Mohammed Farooq (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the success rate of external dacryocystorhinostomy with intramucosal injection and sponge application of Mitomycin C to circumosteal mucosa.Study Design: Quasi-experimental studyPlace and Duration of Study: Eye Department, Combined Military Hospital, Jhelum Cantt Pakistan, from Feb 2019 to Dec 2021.Methodology: One hundred ten patients were selected and randomly allocated into two equal Groups labelled Group-A and Group-B. Group-A patients received 0.1ml of intramucosal injection of 0.02% Mitomycin C, and Group-B patients had 0.02% Mitomycin C applied with a sponge to the circumboreal mucosa. The result of DCR was evaluated at six months and declared successful if the patients were asymptomatic of epiphora and a patent lacrimal passage was found on probing and irrigation. Failure was defined as symptomatic epiphora along with regurgitation on probing and syringing. In failed cases, nasal endoscopy was performed along with probing.Results: Success rates of external dacryocystorhinostomy in the Intramucosal Injection Group was 96%, and in the Sponge Application Group, it was 92%. A comparison of both techniques depicted a statistically insignificant difference in success rate (p=0.60).Conclusion: Mitomycin C use as an adjunctive agent during external dacryocystorhinostomy is a safe and effective technique in achieving a high rate of success, and the route of application, whether applied topically or injected intramucosal does not significantly affect the outcome of this procedure.